2019
DOI: 10.1097/md.0000000000013842
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of high neutrophil-to-lymphocyte ratio in breast cancer patients receiving neoadjuvant chemotherapy

et al.

Abstract: Background:We aimed to evaluate the correlation of neutrophil-to-lymphocyte ratio (NLR) with pathological response, disease-free survival (DFS), and overall survival (OS) in patients with breast cancer and under neoadjuvant chemotherapy (NAC).Materials and methods:We performed a systematical search using Cochrane Library, ScienceDirect, PubMed, Embase, and Web of Science up to May 2018. On the basis of the data directly obtained from the available studies, the odds ratios (ORs) and their 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The NL ratio has been accepted as a predictive biomarker for prognosis in several cancers. In a meta-analysis, a high NL ratio was shown to be statistically significantly associated with poor response to NAC in breast cancer patients [47]. Rivas and colleagues have shown the NL ratio might be a predictive biomarker for tumor response in luminal B breast cancer patients receiving neoadjuvant therapy [48].…”
Section: Discussionmentioning
confidence: 99%
“…The NL ratio has been accepted as a predictive biomarker for prognosis in several cancers. In a meta-analysis, a high NL ratio was shown to be statistically significantly associated with poor response to NAC in breast cancer patients [47]. Rivas and colleagues have shown the NL ratio might be a predictive biomarker for tumor response in luminal B breast cancer patients receiving neoadjuvant therapy [48].…”
Section: Discussionmentioning
confidence: 99%
“…14 Xue et al found that preoperative neutrophil elevation, patients with poor prognosis, short survival time. 15 In Li Sen's study, they found that neutrophils enhance the migration, invasiveness and epithelial-mesenchymal transition (EMT) of gastric cancer (GC) cells through IL-17a ( Figure 1A-C). 16 Under normal circumstances, lymphocytosis is more common in children.…”
Section: Common Hematological Parameters In Peripheral Blood White Blmentioning
confidence: 97%
“…In the last few years, inflammatory blood markers have emerged as predictive and prognostic factors, particularly the neutrophil to lymphocyte ratio (NLR); that is, the ratio between the absolute neutrophil count and the absolute lymphocyte count. Lymphopenia and a high NLR before chemotherapy initiation have been inconsistently associated with worse responses to neo-adjuvant chemotherapy and with poor prognoses of different cancer types, including BC [3,4].…”
Section: Introductionmentioning
confidence: 99%